Mistress of Snow - Sonnenschein, Dana (Gingerbread House Literary Magazine, 2021)
Hinges creak, and she swirls in the door, puts her finger to blue lips. Cold takes the old woodcutter, eyes open, breath frozen in his beard. But crystals melt in your lashes as you gaze on her gl…
Keywords: dept.eng